2021
DOI: 10.14202/vetworld.2021.640-648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen-degradable-to-undegradable protein ratio in ruminant diet on in vitro digestibility, rumen fermentation, and microbial protein synthesis

Abstract: Background and Aim: Feeding ruminants must notice the degradability of feed, especially protein. Microbial rumen requires ammonia from rumen degradable protein (RDP) beside that ruminant require bypass protein or rumen undegradable protein (RUP) and microbial crude protein. The aim of the study was to discover the best RDP:RUP ratio in beef cattle diets commonly used by Indonesian farmers using an in vitro methodology. Materials and Methods: Samples of Pennisetum purpureum, Leucaena leucocephala, Indigofera z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 32 publications
(39 reference statements)
4
40
2
Order By: Relevance
“…Rumen pH was not significantly affected by RDP levels and sulfur supplementation (p>0.05). This is in line with other studies that reported rumen pH did not affect by different RDP levels [27,28] and sulfur supplementation [16,17]. The rumen pH value in all treatments was in the normal range (6.86-7.00) to support the fermentation process.…”
Section: Ruminal Fermentation Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…Rumen pH was not significantly affected by RDP levels and sulfur supplementation (p>0.05). This is in line with other studies that reported rumen pH did not affect by different RDP levels [27,28] and sulfur supplementation [16,17]. The rumen pH value in all treatments was in the normal range (6.86-7.00) to support the fermentation process.…”
Section: Ruminal Fermentation Characteristicssupporting
confidence: 91%
“…The combination between treatments R1 (60% RDP) and S2 (0.1% sulfur supplementation) had the highest total VFA concentration. According to Putri et al [28], increasing total VFA concentration was followed by increasing RDP in the rumen. Total VFA concentration was increased by sulfur supplementation with Na 2 SO 4 due to attributed increasing cellulolytic bacteria population [14].…”
Section: Ruminal Fermentation Characteristicsmentioning
confidence: 98%
“…In this study, MPS was 6.94-7.56 mg/10 mL; this was lower than the range reported by Putri et al [70], who reported a MPS of 10 mg/10 mL produced from a legume-based ration with 16% protein content and different RDPR levels (55:45, 60:40, and 65:35). This difference in MPS is due to the difference in feed ingredients (leguminous vs. concentrate) and types of NFC used in the rations.…”
Section: Rumen Microbes and Mpscontrasting
confidence: 79%
“…The different degradability in the rumen was compensated by different post-ruminal digestibility, which resulted in similar total DMD and OMD. One previous study reported that an increasing RDPR level improves DMD and OMD [70]; this is true for rations high in fiber that rely mainly on rumen fiber degradation, but this was not the case in the current study.…”
Section: Dmd and Omdcontrasting
confidence: 75%
“…The pH value is measured using a pH meter. The concentration of NH3 and total VFA analysis as described in Putri et al (2021). Chemical composition of PLF before and after ammonization can be seen in Table 1.…”
Section: Ammoniation and In Vitro Proceduresmentioning
confidence: 99%